The difficulties encountered by the mothers having children with mental disabilities or autism in participating to community life - (:unkn) unknown (International Journal of Special Education, 2013)
The purpose of the study was to compare the difficulties encountered by the mothers having children with mental disabilities or autism in participating to community life. The participants were 21 mothers who have mentally handicapped child and 21 mothers who have child with autism from Istanbul, Turkey. Data was collected through semi-structured interview technique. Nine community skill areas were determined. The results indicated that the mothers having children with autism had more difficulties in participating to the community life than the mothers having children with mental disabilities. While the mothers having children with mental disabilities declared that they experience most difficulties at visiting their neighbors or close relatives, the mothers having children with autism declared that they experience most difficulties in going to somewhere from another place as a pedestrian. When the declared opinions are analyzed, it is observed that caused to feel unwell by people’s overlook is repeated challenge of the both two groups. © 2013, International Journal of Special Education. All rights reserved.